A hybrid control strategy for a dynamic scheduling problem in transit networks - Liu, Zhongshan; Yu, Bin; Zhang, Li; Wang, Wensi (Zielona Góra: Uniwersytet Zielonogórski)
Public transportation is often disrupted by disturbances, such as the uncertain travel time caused by road congestion. Therefore, the operators need to take real-time measures to guarantee the service reliability of transit networks. In this paper, we investigate a dynamic scheduling problem in a transit network, which takes account of the impact of disturbances on bus services. The objective is to minimize the total travel time of passengers in the transit network. A two-layer control method is developed to solve the proposed problem based on a hybrid control strategy.
Keywords: service reliability; transit network; proactive control method; deep reinforcement learning; hybrid control strategy